Distribution of antibiotic resistant bacteria and genes in sewage and surrounding environment of Tórshavn, Faroe Islands - Mortensen, Anna Maria Steintún; Poulsen, Sissal Jóhanna; Berbisá, Marjun á Fríðriksmørk; Djurhuus, Anni (Frontiers in Environmental Science, 2024)
Several studies have investigated the effects of swimming in sewage-polluted recreational beach water, demonstrating a health hazard. To avoid a potential pathogen transmission pathway, it is imperative that the polluted water is released away from recreational waters and foreshores, where children tend to play. At present, domestic sewage in the Faroe Islands solely undergoes primary wastewater treatment within primary settlings tanks before being discharged into the ocean. Effluents are a major anthropogenic source of antibiotic resistance genes and antibiotic resistant bacteria, which are released into the environment.The aim of this study was to investigate antibiotic resistant gram-negative bacteria and antibiotic resistance genes in influents and effluents of wastewater subjected solely to primary treatment, along with their release into the environment during both summer and winter.Water samples were collected from influents and effluents as well as with increasing distance away from the wastewater outlet and from nearby tidepools. Samples were cultured on MacConkey agar with four different antibiotics for detection of antibiotic-resistant bacteria and antibiotic resistance genes were quantified by droplet digital PCR. All multi-drug resistant bacteria were identified using the API 20E kit.We observed an overall decrease of the abundance of gram-negative bacteria from the effluents compared to influents, however, we observed the opposite trend in the antibiotic resistance genes. Antibiotic resistant bacteria and antibiotic resistance genes in addition to multi-drug resistant bacteria were found in the surrounding oceanic and several terrestrial tidepool samples. Of the multidrug resistant bacteria, we found e.g. E. coli, P. aeruginosa, and A. hydrophila species, which can be pathogenic, potentially causing an infection if encountering a host. These results indicate a relatively wide pollution range of the effluents from the septic tank and treated sewage released into the environment, indicating a potential hazard for both humans and wildlife.